Knowledge Attitude and Practices for Antenatal Care and Delivery of The Mothers of Tea Garden in Jalpaiguri and Darjeeling Districts, West Bengal - Manna, Prabir Kumar; Debasis , De; Ghosh, Debidas (National Journal of Community Medicine, 2011)
The present study aimed to access the influence of socioeconomic factors on antenatal care and delivery practices of the mother of North Bengal. A community-based study was carried out among 1772 families of the 7 blocks of the two districts. Various socio-economic factors were considered for the antenatal care and delivery practices. We also tried to find out the relationship between antenatal check up with perinatal mortality. The study shows that the Muslim mothers, Scheduled tribe mothers, non -educated and mothers with higher age group are less interested about ANC. Family income 2000/- month showing 62.42% ANC coverage. We found that only 7.11% mother used Govt. hospital and 2.65% used private clinic. The mother with medical problems and obstetric problems has high ANC coverage. So, socioeconomic factors significantly influence the antenatal coverage and delivery practices. Hence initiative may be taken at Government and non-government levels to raise knowledge, attitude and practices for the improvement of antenatal care and delivery practices of the mother at these zones.